Development of the Micro, Small and Medium Enterprises (MSME) Sector in Probolinggo Based on Statistical Data - Deddy Junaedi; Rohmawati, Rohmawati; Avinda Diana Rahiliah; Kholifatul Fiardillah; Nuri Asa Kamaliatul Izzi; Hosen, Maria Ulfa (International Journal of Economics, Business and Innovation Research, 2024)
UMKM (Micro, Small, and Medium Enterprises) play a crucial role in Indonesia's economy, as evidenced during the economic crisis of 1997/1998, when many large companies failed while UMKM remained resilient. The success of UMKM in facing this crisis demonstrates their better adaptability, supported by flexible organizational structures and workforce. Probolinggo Regency, known for its rich natural and cultural potential, hosts many UMKM that have developed in both quality and quantity. Entrepreneurs in this region utilize local resources to offer quality products through street vendors, cafes, and restaurants. This study aims to explore the significance of UMKM in a region, identify the factors that hinder and promote UMKM growth, and analyze the development of the UMKM sector in Probolinggo. The analysis indicates that UMKM not only create jobs and improve the living standards of the community but also serve as custodians of local culture. Despite facing various challenges, such as limited capital, managerial skills, and location constraints, support from the government and financial institutions can strengthen UMKM growth. Data shows that after a significant decline due to the COVID-19 pandemic, UMKM in Probolinggo began to show signs of recovery in 2022, with an increase in the number of enterprises. This reflects a positive dynamic in the local economic recovery.